A study on maintenance approach of mosque in Felda / Mohamad Johari Turijan - Turijan, Mohamad Johari (2012)
Mosque is one of the buildings which show the Islamic identity through the structure of dome and tower. The functional of mosque as a place people assemble administration centre and centre of spreading knowledge show that multifunctional have at the mosque. Although, the less concerning on maintenance aspect on mosque especially in the FELDA area. A research has implement through collection information and data from interview session. The objective of research in to study the maintenance approach of mosque in FELDA, investigate and analyze the problems in managing and maintaining mosque in FELDA and make recommendation on how to improve a maintenance approach in mosque in FELDA. The research methodology has been done on mosques in FELDA Wilayah Johor Bahru through interview session and observation. Then, the analysis data from the case studies were find the finding and lastly to give recommendation.